Role of Medication Adherence and Socioeconomic Status in Hypertension Control Among Pakistani Patients - Tauqeer Ahmad, Muhammad Adnan Iqbal (Pakistan Journal of Medical & Health Sciences, 2023)
Background: High blood pressure is a predominant and worldwide health issue and a significant risk factor to heart diseases, stroke, and renal failure. Even with the existence of proper antihypertensive medications, there is a significant percentage of patients who cannot attain blood pressure (BP) control. It is believed that medication compliance and socioeconomic status are key predictors of hypertension care especially in developing nations like Pakistan. Methods: The study was a descriptive cross-sectional study at Allama Iqbal Memorial Teaching Hospital/ KMSMC, Sialkot between January 2022 and December 2022. The sample size of 239 adult hypertensive patients aged over 20 years was used. The structured questionnaire and medical records were used to gather data about the demographic characteristics, clinical variables, adherence to medications, and socioeconomic status. The classification of patients was based on blood pressure measurements with a classification into controlled and uncontrolled BP. IBM SPSS Statistics version 21 was used to perform statistical analysis. Crosstabulation was used to perform Chi-square test (2) in relation to establishing links between variables and BP control; p-value = 0.05 was taken as statistically significant. Results: Among the 239 participants, 66 (27.6%) were males and 173 (72.4%) were females, with a mean age of 55.42 ± 10.11 years. Overall, BP was controlled in 70 (29.3%) patients and uncontrolled in 169 (70.7%) patients. Medication adherence was observed in 111 (6.4%) patients, while 128 (53.6%) were non-adherent. A significant association was found between medication adherence and BP control (p=0.001). Socioeconomic status was also significantly associated with BP control (p=0.006). However, age, gender, educational level, duration of hypertension, comorbidities, and type of antihypertensive drugs were not significantly associated with BP control (p>0.05). Conclusion: Medication adherence and socioeconomic status play significant roles in hypertension control. Improving patient adherence to antihypertensive medications and addressing socioeconomic barriers may enhance blood pressure management and reduce the burden of cardiovascular diseases. Keywords: Hypertension, Blood Pressure Control, Medication Adherence, Socioeconomic Status, Antihypertensive Therapy, Pakistan.